Assessment of spatio-temporal gait parameters in the group of 9 years old healthy children - Szymczyk, Daniel; Majewska, Joanna; Szczepanik, Magdalena; Bazarnik-Mucha, Katarzyna; Snela, Sławomir; Skrzypiec, Julian (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Gait analysis can be defined as a measurement, description and assessment of human locomotion. The development of quantitative gait analysis methods and their increasing application to pathological gait assessment in children has created an urgent need for establishing normative data. The spatio-temporal gait parameters must be compared with valid reference data for the appropriate interpretation. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Objective: The aim of this study was the assessment of the spatio-temporal gait parameters of 9 years old healthy children, considering the subject’s gender and the potential difference between right and left lower limb. Additional purpose of our study was to develop own reference data for the gait analysis in this age group. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: 42 healthy, nine years old children (19 girls, 23 boys), participated in this study. 3D gait analysis was performed using the computerized optoelectronic system (BTS Smart, Italy). Basic spatio-temporal gait parameters (percentage share of the stance and swing phase, right and left lower limb step lenght, as well as step frequency and average gait speed, were anylysed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: Our research showed no statistically significant influence of gender, and no differences between the right and left lower limbs on most of the gait parameters in the study group.